Engineering materials & tribology xxii - Loca, Dagnija (Trans Tech, 2014)
Collection of selected, peer reviewed papers from the 22nd International Baltic Conference of Engineering Materials & Tribology (BALTMATTRIB 2013), November 14-15, 2013, Riga, Latvia. The 72 papers are grouped as follows: Chapter 1: Coatings and Surface Engineering, Chapter 2: Material Mechanics and Tribology, Chapter 3: Functional Materials, Chapter 4: Structural Materials, Chapter 5: Biomaterials Engineering and Application, Chapter 6: Materials for Energy and Environmental Applications, Chapter 7: Powder synthesis and Processing, Chapter 8: Materials Characterization, Chapter 9: Hybrid Mate.